Antioxidant, Antiproliferative and Antimicrobialproperties of Leaf Extmcts of Pereskia Grandifolia,Pereskla Bleo and Polygonum Odoratum Lour - Yusoff, Hafzan (2006)
Malaysia is one of the Asian countries which are endowed with highly diverse biological resources. Indeed, quite high percentage of flora available in this country is believed to have medicinal and nutritional values, Even though a few spesies such as "Kacip Fatimah", "Tongkat Ali" and "Misai Kucing", just to name a few has undergone scientific research, but they are many more need thorough investigation. Studies on the antioxidant, antiproliferative and antimicrobial properties of ethanol leaf extracts of Pereskia bleo, Pereskia grandifolia and Polygonurn odoraturn were undertaken. DPPH assay was carried out to measure the capacity of the extracts to scavenge free radicals, whereas the inhibitions of lipid peroxidation by the extracts were done using p-carotene bleaching method. The phenolics content was quantified using Folin Ciocalteau reagen-t and the correlation between total phenolics content and antioxidant activity was tested. Antiproliferative property of the extracts were assessed using MTT assay on different cancer cell lines, namely CaOV3, HeLa, HepG2 and MDA-MB231, while the antimicrobial property of the extracts were screened using disc diffusion assay. Determination of vitamin A, C, E and mineral contents were also carried out. From both antioxidant assays, these extract showed high antioxidant activities which could be attributed to the occwrence of phenolics. Result obtained from la/f'TT assay showed that the proliferations of &La and Ca(3Y3 cells were eifestiveiy inhibited by the extracts